2011
DOI: 10.1371/journal.pone.0020599
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 and -9 Secreted by Leukemic Cells Increase the Permeability of Blood-Brain Barrier by Disrupting Tight Junction Proteins

Abstract: Central nervous system (CNS) involvement remains an important cause of morbidity and mortality in acute leukemia, the mechanisms of leukemic cell infiltration into the CNS have not yet been elucidated. The blood-brain barrier (BBB) makes CNS become a refugee to leukemic cells and serves as a resource of cells that seed extraneural sites. How can the leukemic cells disrupt this barrier and invasive the CNS, even if many of the currently available chemotherapies can not cross the BBB? Tight junction in endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 43 publications
5
139
1
2
Order By: Relevance
“…Studies have confirmed that MMP-2 and MMP-9 play an important role in the invasion process of various solid tumors (Ray et al, 1994) and are also abnormally expressed in AML; their expression levels are correlated with extramedullary infiltration by leukemia cells (Reikvam et al, 2010). Feng reported that tight junction proteins were more obviously disrupted in SHI-1 cells than in the HL-60 and U937 leukemic cell lines, which is consistent with the higher rate of invasion of SHI-1 cells and the high constitutive expression of MMP-2 and MMP-9 in this cell line (Feng et al, 2011;Wang et al, 2010). MMP-2 and MMP-9 are tightly regulated at the levels of transcription and secretion by multiple factors.…”
Section: Discussionmentioning
confidence: 53%
“…Studies have confirmed that MMP-2 and MMP-9 play an important role in the invasion process of various solid tumors (Ray et al, 1994) and are also abnormally expressed in AML; their expression levels are correlated with extramedullary infiltration by leukemia cells (Reikvam et al, 2010). Feng reported that tight junction proteins were more obviously disrupted in SHI-1 cells than in the HL-60 and U937 leukemic cell lines, which is consistent with the higher rate of invasion of SHI-1 cells and the high constitutive expression of MMP-2 and MMP-9 in this cell line (Feng et al, 2011;Wang et al, 2010). MMP-2 and MMP-9 are tightly regulated at the levels of transcription and secretion by multiple factors.…”
Section: Discussionmentioning
confidence: 53%
“…Consistently, genetic or pharmacological inhibition of cathepsin S significantly impaired the development of experimental breast-to-brain metastasis . Similarly, degradation of the tight junction proteins claudin-5 and occludin by MMP2 and MMP9 secreted by leukemic cells led to BBB breakdown and contributed to CNS involvement in acute leukemia (Feng et al 2011). As these representative examples indicate, proteases can promote invasion and metastasis to multiple organ sites through a plethora of different molecular mechanisms.…”
Section: Invasion and Metastasismentioning
confidence: 99%
“…Feng and others have hypothesized that matrix metalloproteinases secreted by leukemic cells may facilitate the breakdown of the blood-brain barrier (BBB), which may lead to seeding of the CSF during transient bacteremia (20). Additionally, melanoma is known to disrupt the BBB, and in our patient, disruption of the BBB by metastatic melanoma might have facilitated P. acnes to enter the CSF; however, it is unclear why P. acnes and not another organism might cause disease in this setting (21,22).…”
Section: Case Reportmentioning
confidence: 99%